2022
DOI: 10.1159/000524804
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Factor Pathway Inhibitor 2: A Novel Biomarker for Predicting Asymptomatic Venous Thromboembolism in Patients with Epithelial Ovarian Cancer

Abstract: <b><i>Objectives:</i></b> Patients with asymptomatic venous thromboembolism (VTE) are associated with an increased risk of pulmonary thromboembolism events. However, due to low specificity and high false-positive rates, D-dimer testing cannot be used alone to diagnose VTE. Tissue factor pathway inhibitor 2 (TFPI2), a new serodiagnostic marker for ovarian cancer, plays a role in blood coagulation system regulation. We hypothesized that combining D-dimer and TFPI2 would improve its utilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(28 citation statements)
references
References 28 publications
1
27
0
Order By: Relevance
“…A multicenter prospective cohort study revealed that TFPI2 is a novel serum biomarker for predicting ovarian cancer [9]. Furthermore, ovarian cancer patients who experienced VTE had elevated TFPI2 levels compared to those without thromboembolic events, suggesting that TFPI2 may be a biologic marker for predicting VTE [15,16]. A better understanding of the biological functions of TFPI2 may help develop optimal therapeutic strategies not only for cancer and VTE, but also for preeclampsia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A multicenter prospective cohort study revealed that TFPI2 is a novel serum biomarker for predicting ovarian cancer [9]. Furthermore, ovarian cancer patients who experienced VTE had elevated TFPI2 levels compared to those without thromboembolic events, suggesting that TFPI2 may be a biologic marker for predicting VTE [15,16]. A better understanding of the biological functions of TFPI2 may help develop optimal therapeutic strategies not only for cancer and VTE, but also for preeclampsia.…”
Section: Discussionmentioning
confidence: 99%
“…Third, there is clinical evidence that TFPI2 contributes to promoting the thrombus formation. Indeed, in patients with ovarian cancer, elevated serum TFPI2 levels were reported to be associated with an increased risk of VTE [15,16]. A multivariate analysis showed that a cut-off value of 12.5 pM for TFPI2 was an independent risk factor for VTE.…”
Section: The Functional Diversity Of Tfpi2mentioning
confidence: 98%
See 1 more Smart Citation
“…To overcome this bias, a multi-center prospective cohort study is now proceeding (UMIN000034969). Second, the newly reported tumor marker of tissue factor pathway inhibitor 2 (TFPI2) was not assessed [ 74 , 75 ]. Finally, we did not compare diagnostic efficacy among the IOTA classification, ROMA index, the CPH index, and the e-NARA index.…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, TFPI2 was significantly elevated in ovarian cancer patients with VTE compared with non-VTE patients, suggesting that it is actually associated with VTE risk. 11,12 In addition, elevated serum TFPI2 levels have also been reported in patients with preeclampsia [13][14][15] and atherosclerosis. 16 Since TFPI2 inhibits the TF-mediated coagulation pathway, we initially thought that, like TFPI1, elevated TFPI2 would suppress thrombus formation.…”
Section: Introductionmentioning
confidence: 97%